Challenges in nature-based health and therapy research and critical considerations for application in musculoskeletal health - Doran-Sherlock, Richard; Sood, Payal; Struthers, Nicole Anne; Maric, Filip (Frontiers in Public Health, 2025)
Nature-based health and therapy (NBHT) is a term incorporating a broad suite of practices that focus on engagement with the natural world and nature-rich spaces for potential physical and mental health benefits. As healthcare professions such as physiotherapy and osteopathy move away from biomedical/reductionist models of care for complex conditions towards approaches which take into account social and environmental determinants of health, NBHT may become part of clinical interventions and public health messaging. However, there are multiple challenges in aspects of NBHT research and application, from methodological issues in the primary research base, to questions of environmental injustice and access inequalities in many areas. In addition, engaging with natural environments which are vulnerable to the entwinned threats of climate change and biodiversity collapse requires consideration of the effects of ecological disturbance and the underlying anthropocentric/utilitarian view of the natural world. In this perspective, we outline a critique of NBHT literature and offer positive suggestions for how better-quality research can be conducted and implemented by focusing on local environmental, social, and political factors. We conclude by outlining a set of critical considerations that healthcare professionals might use to develop and implement NBHT programmes in their specific regional contexts.